Life is a Gift : Loving You - Karamjeet Kaur; Tants, Karen; Cartwright, Kathryn; Magee, Geri, Dr.; Chardonai; Rose, Isabella; Parminder Kaur Sarai; Aune, Christopher; Munira Zahabi; Sturgeon, Sundi, Dr.; Heathcote, Mark; deCaussin, Susan; et al. (Selangor : Karamjeet Kaur, 2020)
Life is a Gift ~ Loving You, is a beautiful anthology compilation of stories by the Self-Love Specialist, Karamjeet Kaur. Life is a Gift covers a wide range of subjects aimed at teaching one how to love oneself unconditionally along the journey through life....
Keywords: Self-actualization (Psychology); Self -- Acceptance; Self-esteem